On the Sixth Power Mean of the Two-term Exponential Sums - Zhang, Wen Peng; Meng, Yuan Yuan (Acta mathematica Sinica. English series, 2022)
The main purpose of this article is to study the calculating problem of the sixth power mean of the two-term exponential sums, and give an interesting calculating formula for it. At the same time, the paper also provides a new and effective method for the study of the high order power mean of the exponential sums.